Potential effects of the United Kingdom’s departure from the European Union on South African citrus exports : a case of non-tariff measures - Kalaba, Mmatlou W. (University of Pretoria, 2021)
Dissertation (MSc (Agric) (Agricultural Economics))--University of Pretoria, 2021.